2005
DOI: 10.1001/archderm.141.8.963
|View full text |Cite
|
Sign up to set email alerts
|

UV Light Tanning as a Type of Substance-Related Disorder

Abstract: To better understand the complex motivations involved with UV light (UVL) tanning behavior.Design: Two written instruments, the CAGE (Cut down, Annoyed, Guilty, Eye-opener) Questionnaire, used to screen for alcohol abuse or dependence, and the American Psychiatric Association Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision (DSM-IV-TR) criteria for substance-related disorders, were modified to evaluate subjects for a substance-related disorder involving UVL tanning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
141
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(152 citation statements)
references
References 20 publications
(14 reference statements)
9
141
0
Order By: Relevance
“…Teenagers who frequently tan indoors selfreport difficulty in quitting tanning and 53 % of frequent tanners evaluated in one study met official criteria for a UVR-associated substance-related disorder. 1 Another study demonstrated withdrawal-like symptoms in 50 % of frequent tanners when given the opioid antagonist naltrexone. 2 Physiologically, UVR induces expression of p53, stimulating the pro-opiomelanocortin (POMC) promoter to produce α-melanocyte-stimulation hormone, which promotes melanogenesis and causes pigmentation, and β-endorphin, an endogenous opioid that might account for the so-called "tanner's high."…”
Section: Indoor Tanning Dependencymentioning
confidence: 99%
“…Teenagers who frequently tan indoors selfreport difficulty in quitting tanning and 53 % of frequent tanners evaluated in one study met official criteria for a UVR-associated substance-related disorder. 1 Another study demonstrated withdrawal-like symptoms in 50 % of frequent tanners when given the opioid antagonist naltrexone. 2 Physiologically, UVR induces expression of p53, stimulating the pro-opiomelanocortin (POMC) promoter to produce α-melanocyte-stimulation hormone, which promotes melanogenesis and causes pigmentation, and β-endorphin, an endogenous opioid that might account for the so-called "tanner's high."…”
Section: Indoor Tanning Dependencymentioning
confidence: 99%
“…Knowledge about the dangers of UVR often does not change tanning behavior. 24,25 These practices may persist because many people believe that a tanned appearance is attractive and healthy. In 1 study, 67.8% of youth agreed with the statement "I look better when I have a tan" and 55% agreed with the statement "I feel healthy when I have a nice tan."…”
Section: Why People Tanmentioning
confidence: 99%
“…Several approaches to measuring tanning dependence have been taken. Warthan and colleagues (Warthan, Uchida, & Wagner, 2005) modified the substance dependence criteria from the DSM-IV and those of the four-item CAGE scale, traditionally used to screen for potential problems with alcohol use. The modified seven-item DSM-IV criteria include tolerance, withdrawal, and engaging in the behavior despite negative consequences, key criteria for the diagnosis of substance dependence.…”
Section: Tanning Dependencementioning
confidence: 99%
“…Among tanning salon patrons in the US, tanning dependence rates range from 33-41% . Among beachgoers, rates range from 26-53% (Warthan et al, 2005). Rates are 22-45% among undergraduate indoor tanners (Heckman, Egleston et al, 2008;Mosher & Danoff-Burg, 2010a, 2010bPoorsattar & Hornung, 2007).…”
Section: Tanning Dependencementioning
confidence: 99%